On the variation of gender characteristics of declinable common nouns - Boltovskaya, Elena A. (Journal of the Belarusian State University. Philology, 2023)
On the basis of normative grammar workbooks, grammar reference books and thesaurus dictionaries of different time periods, the changes in gender affiliation of common nouns that occurred from the second half of the 20th until the beginning of the 21st century have been revealed and characterised. The fluctuations between the masculine and feminine genders of declinable nouns with a stem ending in a hard and soft consonant have been considered. It has been established that the reduction of gender variants associated with semantic or stylistic differences occurs both in the direction of masculine and feminine (less often) genders. The results of the study can be used in the process of teaching modern Russian literary language morphology, stylistics and speech culture, and Russian literary language history.
Keywords: literary norm; declinable common nouns; the gender of the noun; dual gender relation; clashing of gender variants